(untitled) (Oxford, 1992)
This volume is a comprehensive view of strategic management in Japan. The book begins with a general view of Japanese management style, and considers how this style affects strategic management. Specifically, the Japanese approach to research and development is considered. Another important aspect is the discussion of how the Japanese bring subsidiary companies in other countries into their strategic plans, asking the question to what extent can Japanese management style be effective outside of Japan.
Keywords: Kế hoạch chiến lược,Strategic planning; Nhật Bản,Japan